The Effect of Adverse and Positive Childhood Experiences, Attachment, and Emotional Support on Adult Mental Health - Metka Kuhar; Elizabeth Dorrance-Hall; Simona Prosen (European Journal of Mental Health)
Introduction: Adverse childhood experiences (ACEs) can contribute to significant health issues in adulthood.